The Role of Religious Moderation Values in Enhancing the Community’s Economic Development in Pontianak - Yuliani, Sri (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2025)
This study aims to analyze the role of religious moderation values in improving the community’s economy in Pontianak City. Religious moderation encompasses tawassuth (moderation), tasamuh (tolerance), ta’awun (cooperation), and i’tidal (justice), which are believed to foster social harmony and promote economic productivity. The research employs a quantitative approach with a descriptive–correlational method. The population consists of active economic actors in Pontianak, with a sample of 385 respondents selected using proportional random sampling. Data were collected through a Likert-scale questionnaire, interviews, and secondary documentation, and were analyzed using descriptive statistics and simple linear regression. The results indicate that religious moderation is at a high level (mean score = 4.23), while community economic improvement is also high (mean score = 4.11). Regression analysis shows a positive and significant relationship, with R² = 0.451 and the equation Y = 1.247 + 0.689X, indicating that the internalization of religious moderation values explains 45.1% of the variation in community economic improvement. This study concludes that religious moderation plays a vital role in promoting an inclusive, ethical, and sustainable community-based economy. Practically, the findings provide a basis for local economic development policies, while theoretically, they enrich interdisciplinary studies linking economics, society, and religion.